Comparison of intrarectal ozone, ozone administered in acupoints and meloxicam for postoperative analgesia in bitches undergoing ovariohysterectomy - Teixeira, L. R.; Luna, Stélio Pacca Loureiro [UNESP]; Taffarel, M. O. [UNESP]; Lima, A. F M [UNESP]; Sousa, N. R. [UNESP]; Joaquim, J. G F [UNESP]; Freitas, P. M C (Elsevier, 2013)
Since all analgesics currently available for use in dogs have been associated with some adverse effects, the search for an effective analgesic that does not cause harm is important. This study investigated the postoperative analgesic effects of ozone administered either intrarectally or into acupoints in bitches undergoing ovariohysterectomy (OH). Twenty-four healthy adult bitches were randomly assigned to one of the three treatments 10min after sedation, as follows: 0.2mg/kg of intramuscular (IM) meloxicam (M); rectal insufflation of 10mL of 30μg/mL ozone (OI), or acupoint injection of 0.5mL ozone (30μg/mL; OA). Following sedation with acetylpromazine, anaesthesia was induced with propofol and fentanyl and maintained with isoflurane/O2. Pain was assessed using the modified Glasgow pain scale (MGPS) and the visual analogue scale (VAS) on the day before surgery, before anaesthesia, and at 1, 2, 4, 6, 8, 12 and 24h after surgery. Rescue analgesia was performed using 0.5mg/kg of morphine IM if MGPS was >3.33 points.No statistically significant differences in pain scales were found among the three analgesic protocols or the time points in each group ( P>. 0.05). Two dogs treated with OA required rescue analgesia. Meloxicam, rectal insufflation of ozone and ozone injected into acupoints provided satisfactory analgesia for 24. h in bitches undergoing elective OH. Ozone had no measurable adverse effects and is an alternative option to promote pain relief. © 2013 Elsevier Ltd.
Keywords: Dogs; Hysterectomy; Ozone; Pain; Postoperative